siRNA selection criteria--statistical analyses of applicability and significance - Bradáč, Ivan; Svovodová-Vareková, Radka; Wacenovky, Michael; Škrdla, Michal; Plchút, Martin; Polčík, Martin (Biochemical and biophysical research communications, 2007)
RNA interference is a powerful tool for gene silencing, which is mediated by introducing siRNA. In the present study, statistical analyses of published siRNA selection criteria, the interpretation of some criteria and systematic searching for new criteria have been carried out for CGB siRNA and siRecords databases. The results of the analyses are as follows: (i) Our study supports the two-state model of the RNA-induced silencing complex (RISC). (ii) Stable 5'-S ends of a siRNA sequence, higher stability of the whole siRNA, and low breaking energy of siRNA duplex occurs in effective siRNA sequences. Also low internal stability of the 5'-AS terminus is preferred. (iii) Secondary structure can be successfully used as an RNAi selection criterion. (iv) Several published sequence criteria have been confirmed and also new criteria have been developed. (v) Also a Target Patterns criterion, which is comparable or better than the best known criteria, has been created.
Keywords: Sequence Analysis, RNA; Gene Silencing; Models, Genetic; RNA, Small Interfering; Molecular Sequence Data; Data Interpretation, Statistical; sekvenční analýza RNA; Models, Statistical; modely genetické; interpretace statistických dat; molekulární sekvence - údaje; sekvence nukleotidů; Base Sequence; umlčování genů; malá interferující RNA; statistické modely; Financing, Organized; financování organizované